On Jordan Generalized Reverse Derivations on -rings - Mehdi Salih, Salah; Riyadh Salih, Marwa (Iraqi Journal of Science, 2023)
In this paper, we study the concepts of generalized reverse derivation, Jordangeneralized reverse derivation and Jordan generalized triple reverse derivation on -ring M. The aim of this paper is to prove that every Jordan generalized reversederivation of -ring M is generalized reverse derivation of M.